Health care use in response to health shocks: Does socio‐economic status matter?. (12th September 2021) - Fiebig, Denzil G.; van Gool, Kees; Hall, Jane; Mu, Chunzhou
Abstract: We investigate how utilization of primary care, specialist care, and emergency department (ED) care (and the mix across the three) changes in response to a change in health need. We determine whether any changes in utilization are impacted by socio‐economic status. The use of a unique Australian data set that consists of a large survey linked to multiple years of detailed administrative records enables us to better control for individual heterogeneity and allows us to exploit changes in health that are related to the onset of two health shocks: a new diagnosis of diabetes and heart disease. We extend the analysis by also examining changes to patient out‐of‐pocket costs. We find significant differences in the mix between primary and specialist care use according to income and type of health shock but no evidence of using ED as a substitute for other care. Our results indicate that low‐ and high‐income patients navigate very different pathways for their care following the onset of diabetes and to a lesser extent heart disease. These pathways appear to be chosen on the basis of ability to pay, rather than the most effective or efficient bundle of care delivered through a combination of GP and specialist care.